1993
DOI: 10.1073/pnas.90.15.6949
|View full text |Cite
|
Sign up to set email alerts
|

Alloantibodies can discriminate class I major histocompatibility complex molecules associated with various endogenous peptides.

Abstract: Molecules encoded by a single major histo- (7)(8)(9). These molecules can be exogenously loaded with a single type of synthetic peptide thereby creating a situation in which all class I-peptide complexes on the cell surface are identical. In a set of recent reports, we (10) and others (11) observed that loading unoccupied Kb molecules with different synthetic peptide antigens altered their recognition by alloantibodies. For instance, the Kb-specific monoclonal antibody (mAb) SF1.2 bound Kbovalbumin peptide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…This hypothesis also is not very likely. Third, HLA conformational changes induced by peptides may alter serological epitopes and inhibit mAb recognition (6)(7)(8)(9)(10)(11)(12)(13)28). Previous crystallographic analysis of HLA-A2, -B8, and -A11 molecules have shown subtle structural differences when various peptides are introduced in the binding groove (20,22,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis also is not very likely. Third, HLA conformational changes induced by peptides may alter serological epitopes and inhibit mAb recognition (6)(7)(8)(9)(10)(11)(12)(13)28). Previous crystallographic analysis of HLA-A2, -B8, and -A11 molecules have shown subtle structural differences when various peptides are introduced in the binding groove (20,22,29).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been mainly documented with murine anti-H2-K b , -K d , and -L d mAbs by testing the expression on mutant cells of class I MHC molecules loaded with synthetic peptides or by performing selective immunoprecipitation of complexes containing different sets of peptide. In those studies, specific residues of the bound peptide essential for mAb recognition were identified, and the impact of exposed, but also buried, peptide residues on ␣1 and ␣2 MHC conformation was demonstrated (6)(7)(8)(9)(10)(11)(12). The same effect of peptides on mAb recognition of HLA class I molecules also has been observed by studying HLA-B27, -A11, or -B35/-B51 molecules loaded with various peptides and their analogues' ligands.…”
mentioning
confidence: 99%
“…MHC class I molecules were found to acquire different conformations when different peptides were bound. Those changes were reflected by changes in the binding of anti-class I mAb (12)(13)(14)(15). Crystallization of MHC class I with different peptides enabled the detailed analysis of such changes (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It is well appreciated that peptides are able to change the conformation of MHC class I molecules. These changes were detected as gain͞loss of binding by anti-class I antibodies (12)(13)(14)(15) and by analysis of MHC class I molecules crystallized with single peptides (16,17). We sought to determine whether peptide-dependent changes occur in MHC class II that could be detected by mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study with K b -specific mAbs showed that by increasing the number of peptides, a larger number of K b -reactive mAbs appear to be peptide dependent. Peptide pools eluted from K b molecules that were immunoprecipitated with a peptide-selective mAb were successfully used to reconstitute empty K b molecules on T2-K b targets that were lysable by some allo-CTL clones (17). This suggests a relationship between alloreactive CTL and alloantibody recognition of MHC class I.…”
Section: Discussionmentioning
confidence: 99%